Sustainable Agricultural Development In Indonesia (Article Review) - Fikriman Fikriman; Eci Prayetni; Pitriani Pitriani (Fakultas Pertanian Universitas Muara Bungo, 2022)
ABSTRACTThe definition of sustainable agriculture is the successful management of resources for agricultural enterprises to meet changing human needs while maintaining or improving environmental quality and conserving natural resources. The true meaning of sustainable agriculture is one that is economically sustainable which is achieved by: less energy use, minimal ecological footprint, less packaged goods, widespread local purchasing with shorter food supply chains, less processed foodstuffs, community gardens and gardens more houses, and so on Sustainable agriculture relies heavily on returning nutrients to the soil by minimizing the use of non-renewable natural resources such as natural gas (which is used as a feedstock for fertilizers) and minerals (such as phosphates). The most important factors in the utilization of natural resources in a land are soil, sunlight, air, and water.Sustainable agriculture is the implementation of the concept of sustainable development in the agricultural sector. The concept of sustainable agriculture is based on three pillars: economic, social, and ecological.Keywords: Development, Agricultural, Sustainable